From scientific theory to classroom practice. - Dommett, E; Devonshire, I; Plateau, C; Westwell, MS; Greenfield, S (2011)
The importance of neuroscience in education is becoming widely recognized by both neuroscientists and educators. However, to date, there has been little effective collaboration between the two groups, resulting in the spread of ideas in education poorly based on neuroscience. For their part, educators are often too busy to develop sufficient scientific literacy, and neuroscientists are put off collaborations with risk of overinterpretation of their work. We designed and led a successful 6-month collaborative project between educators and neuroscientists. The project consisted of a series of seminars on topics chosen by both parties such as the neuroscience of attention, learning, and memory and aimed to create a dialog between the two. Here, we report that all teachers found the seminars relevant to their practice and that the majority felt the information was presented in an accessible manner. Such was the success of the project that teachers felt there were direct changes in their classroom practice as a consequence and that the course should be more widely available. We suggest that this format of co-constructed dialog allows for lucrative collaborations between neuroscientists and educators and may be a step to bridging the waters that separate these intrinsically linked disciplines.